Complementary Rhizosphere Microbial Strategies Drive Functional Specialization in Coastal Halophyte Succession: Differential Adaptation of Suaeda glauca and Phragmites communis to Saline–Alkali Stress - Hao Dai; Mingyun Jia; Jianhui Xue; Zhuangzhuang Liu; Dongqin Zhou; Zhaoqi Hou; Jinping Yu; Shipeng Lu (Microorganisms)
While rhizosphere microbiome functions in saline soils are well documented, complementary microbial strategies between pioneer and late-successional halophytes remain unexplored. Here, we used 16S rRNA sequencing and FAPROTAX functional prediction to compare the rhizosphere bacterial communities of two key halophytes—Suaeda glauca and Phragmites communis—in a reclaimed coastal wetland. The results demonstrate that both plants significantly restructured microbial communities through convergent enrichment of stress-tolerant taxa (Firmicutes, Pseudomonas, Bacillus, and Planococcus) while suppressing sulfur-oxidizing bacteria (Sulfurovum and Thiobacillus). However, they exhibited distinct microbial specialization: S. glauca uniquely enriched organic-matter-degrading taxa (Promicromonospora and Zhihengliuella) and upregulated aromatic compound degradation (2.29%) and ureolysis (0.86%) according to FAPROTAX analysis, facilitating carbon mobilization in early successional stages. Notably, P. communis selectively recruited nitrogen-cycling Serratia, with increased nitrate respiration (3.51% in P. communis vs. 0.91% in S. glauca) function, reflecting its higher nitrogen demand. Environmental factors also diverged: S. glauca’s microbiome correlated with potassium and sodium, whereas P. communis responded to phosphorus and chloride. These findings uncover distinct microbial recruitment strategies by halophytes to combat saline stress—S. glauca–P. communis synergy through microbial carbon-nitrogen coupling—offering a template for consortia design in saline soil restoration.